PENGEMBANGAN MEDIA DAN SUMBER BELAJAR FILM PENDEK KOLABORASI (COLLABORATIVE SHORT MOVIE) PADA MATERI MITIGASI BENCANA ALAM DI SMA PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Wahyu Nanda Putra; Nofrion Nofrion (JURNAL BUANA, 2020)
This research aims to 1) Produce video media and collaborative short film learning resources on natural disaster mitigation material for XI IPS 3 at the SMA Pembangunan Laboratorium Universitas Negeri Padang, 2) Know the feasibility of video media and collaborative short film learning resources on natural disaster mitigation materials for students of class XI IPS 3 SMA Pembangunan Laboratorium Universitas Negeri Padang. The design of this research is research and development (Research and Development). The research subjects were 25 students of class XI IPS 3 and the object of research was the media and learning resource of collaborative short films on natural disaster mitigation material for students of class XI IPS 3 at SMA Pembangunan Laboratorium. The product development model used is Borg and Gall with simplified steps, namely: 1) Planning: material analysis and RPP analysis, 2) Product Draft Development: Pre-production, Production, and Post-Production, 3) Expert validation: by expert media and material experts, 4) Feasibility Test: by media experts, materials and students. Data collection methods by observation, questionnaire and documentation. The feasibility assessment involved media experts, material experts and students of class XI IPS 3 at the SMA Pembangunan Laboratorium Universitas Negeri Padang. Data analysis techniques using descriptive statistics. The results of the study show that: 1) Video media and learning resources are produced in the form of collaborative short films on natural disaster mitigation materials that are in accordance with the material and lesson plans used at the SMA Pembangunan Laboratorium Universitas Negeri Padang, 2) Test results the feasibility of material experts in the feasible category with a relative frequency of 100% and, media experts in the feasible category with a relative frequency of 80% so that this media is worthy of being tested on students. From the results of trials on 25 students of class XI IPS 3 the results were 91.7% classified in the category of very feasible, thus stating the media and learning resources of short films on natural disaster mitigation materials are appropriate to be used as media and learning resources for students of class XI IPS 3 in SMA Pembangunan Laboratorium Universitas Negeri Padang.